Regional and Gender-Based Distribution of KRAS Mutations in Metastatic Colorectal Cancer Patients in Turkey: An Observational Study - Nurullah Ilhan; Faysal Dane; Erdem Goker; Kazım Uygun; Bülent Orhan; Kerem Okutur; İlkay Tuğba Ünek; Abdurrahman Işıkdoğan; Ahmet Bilici; Nurullah Zengin; Necati Alkış; İdris Yücel; et al. (Medicina)
Background and Objectives: KRAS genes are among the most prominent oncogenes that trigger tumor formation in colorectal cancer (CRC) and serve as predictive biomarkers for resistance to anti-EGFR therapies in metastatic colorectal cancer (mCRC) patients. However, the prevalence and mutation spectrum of the KRAS gene family in mCRC patients in Turkey have not been sufficiently analyzed. This study investigates the frequency and distribution of mutations in the KRAS gene family across different regions of Turkey and examines gender-related variations. Materials and Methods: This multicenter observational study included 2458 histologically confirmed mCRC patients collected from 52 centers across Turkey. In a central laboratory, KRAS mutations in codons 12 and 13 were analyzed using polymerase chain reaction (PCR). Statistical analyses were performed using chi-square tests and Monte Carlo simulations, with a significance threshold set at p < 0.05. Results: Depending on the region, KRAS mutations were detected in 45% of patients, ranging from 39.6% to 47.5%. The mutation rate was significantly higher in female patients (48.8%) compared to male patients (42.6%) (p = 0.002). Codon 12 mutations were more frequent than codon 13 mutations. G12D, G12V, and G13D mutations accounted for 80% of all detected mutations. The G12V mutation was prevalent in female patients (p = 0.007). Based on region, mutation diversity was similar, and no statistically significant difference was found (p > 0.05). Conclusions: This large-scale, multicenter study provides the most comprehensive dataset of KRAS mutations in mCRC patients in Turkey. This study revealed regional trends, as well as gender differences. The findings highlight the importance of routine KRAS genotyping in guiding personalized treatment strategies, especially regarding candidate selection for anti-EGFR therapies. Further research is required to elucidate the prognostic and therapeutic implications of specific KRAS mutations.